Methods of Teaching the Russian Language for Groups in the Direction of "Technology of Pre-Processing of Natural Fibers" (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article explores innovative methods for teaching the Russian language to groups specializing in "Technology of Pre-processing of Natural Fibers". It emphasizes an interdisciplinary approach, integrating language learning with technical content to enhance both linguistic and professional skills. Techniques such as Content-Based Instruction (CBI), collaborative projects, and role-playing are discussed to facilitate vocabulary acquisition and practical application of language skills in technical contexts. The article also highlights the use of multimedia resources, industry interactions, and immersion experiences to provide a comprehensive and engaging learning environment. This approach not only improves language proficiency but also deepens understanding of fiber processing technologies.